A Methodology to Identify a Cohort of Medicare Beneficiaries Residing in Large Assisted Living Facilities Using Administrative Data - Thomas, Kali S; Dosa, David; Gozalo, Pedro L; Grabowski, David C; Nazareno, Jennifer; Makineni, Rajesh; Mor, Vincent (Medical care, 2018)
Assisted living is a popular option for housing and long-term care. To develop and test a methodology to identify Medicare beneficiaries residing in assisted living facilities (ALFs). We compiled a finder file of 9-digit ZIP codes representing large ALFs (25+ beds) by matching Outcome and Assessment Information Set (OASIS) assessments and Medicare Part B Claims to the Medicare enrollment records and addresses of 11,751 ALFs. Using this finder file, we identified 738,567 beneficiaries residing in validated ALF ZIP codes in 2007-2009. We compared characteristics of this cohort to those of ALF residents in the National Survey of Residential Care Facilities (n=3009), a sample of community-dwelling Medicare beneficiaries (n=33,025,690), and long-stay nursing home residents (n=1,287,572). A national list of licensed ALFs, Medicare enrollment records, and administrative health care databases. The ALF cohort we identified had good construct validity based on their demographic characteristics, health, and health care utilization when compared with ALF residents in the National Survey of Residential Care Facilities, community-dwelling Medicare beneficiaries, and long-stay nursing home residents. Our finder file of 9-digit ZIP codes enables identification of ALF residents using administrative data. This approach will allow researchers to examine questions related to the quality of care, health care utilization, and outcomes of residents in this growing sector of long-term care.